Management of dual-purpose wheat genotypes by rotatinuous stocking (Research, Society and Development, 2022)
The objective was to evaluate whether rotatinuous stocking management in dual-purpose wheat genotypes provides greater forage performance compared to the traditional rotational grazing management, which could become an alternative to ryegrass, once this new management strategy has been validated. Three dual-purpose wheat cultivars (BRS Pastoreio, BRS Tarumã and BRS Tarumaxi) and a black oat cultivar (Embrapa 139 Neblina) were used in the experiment, in traditional rotational and rotatinuous stocking. The experiment was carried out in a randomized complete blocks design, with treatments arranged in a 4 x 2 factorial scheme (cultivars x management strategies), with pre and post-harvest heights in traditional rotational management (RT) of  25 and 5 cm, and 25 and 15 in the rotatinuous stocking management (RN). The experiment was carried out at Embrapa Trigo, in Passo Fundo, Rio Grande do Sul state, southern Brazil. Nitrogen was applied after sowing and after cuts, according to the management strategies. Dry matter yield, percentage of leaf blades and forage accumulation per cut and total were evaluated. Wheat cultivars in rotatinuous stocking management showed higher numbers of cuts, greater cycle, percentage of leaves and average rate of forage accumulation, with smaller intervals between cycles. The total forage production showed no difference between the cultivars, however, BRS Tarumaxi was higher in the rotatinuous stocking management. Thus, responses between the genotypes in relation to the management strategies adopted are different.